A Single‐Chamber System of Initiated Chemical Vapor Deposition and Atomic Layer Deposition for Fabrication of Organic/Inorganic Multilayer Films1 . Issue 6 (10th March 2017) - Kim, Bong Jun; Park, Hongkeun; Seong, Hyejeong; Lee, Min Seok; Kwon, Byoung‐Hwa; Kim, Do Heung; Lee, Young Il; Lee, Hyunkoo; Lee, Jeong‐Ik; Im, Sung Gap
Abstract : A single‐chamber system capable of depositing both organic and inorganic layers by initiated chemical vapor deposition (iCVD) and atomic layer deposition (ALD) is demonstrated to facilitate the fabrication of organic/inorganic hybrid thin film encapsulation (TFE). The chamber geometry and the process conditions of iCVD and ALD are similar to each other, which enabled the design of the single‐chamber system. Both organic and inorganic films deposited via the single‐chamber system produces films with their properties equivalent to those deposited in separate iCVD and ALD reactors. Alternating the deposition mode between iCVD and ALD produces organic/inorganic multilayers with outstanding barrier properties as well as optical transparency mechanical flexibility. Abstract : A single‐chamber system that can conduct both initiated chemical vapor deposition (iCVD) and atomic layer deposition (ALD) is demonstrated in this study. From the single‐chamber system, thin film encapsulation (TFE) composed of alternating organic and inorganic layers is fabricated. The TFE exhibited outstanding properties suitable for encapsulation of organic light‐emitting diodes.